Analisis Kualitas Pelayanan Pada Bisnis Retail (Studi Kasus Alfamart Maesan Bondowoso) - alfiyah, siti (INAIFAS Press, 2023)
Service quality is an important factor in the retail business, and is something consumers pay attention to when making decisions. Several factors can influence the purchasing decision in terms of the quality of the service. The success of a retail business is to provide satisfaction to customers associated with an assessment of service quality. By using service quality analysis in the retail business at Alfamart Maesan, the researchers obtained the following results. Service quality plays an important role in building customer satisfaction in a company, service is the spearhead of a service company that will deal directly with consumers or customers. Corporate image is one of the things that needs to be considered in a company, a company must be able to instill a positive image for the company and must also have the ability to assist companies in understanding that customers are important assets that must be maintained and maintained. This method uses a qualitative analysis approach to service quality in the retail business at Alfamaret Maesan.